Mobilisation of Joint-resident Mesenchymal Stromal Cells for Articular Cartilage Regeneration - Khan, Alam Khalil (Orthop J Sports Med, 2017)
BACKGROUND AND OBJECTIVES: Microfracture is a recognized procedure used to treat isolated cartilage injuries or defects, in which bone marrow mesenchymal stromal cells (BM-MSCs) are thought to migrate into the resulting blood clot, leading to subsequent cartilage repair via fibrocartilage formation. The discovery of MSCs in the synovium and synovial fluid (SF) provides a potential mechanism for repairing cartilage from the top down via their migration and homing to the microfracture site, however SF-MSCs low in number and usually lost with joint irrigation. The purpose of this work was threefold; first to test the hypothesis that SF-MSCs can be replaced, and also their numbers further increased by synovial agitation, second that these cells were capable of rapid adhesion to clots and third that the clot composition improve MSC migration. MATERIALS-METHODS: Ex-vivo mechanical agitation of human superficial synovium and in vivo intra-operative agitation of synovium in patients undergoing arthroscopy were performed using a Cytology brush and custom designed Synovial brush. Colony-forming unit-fibroblast (CFU-F) assay was performed to quantify released MSCs. Adhesion to clots was studied by comparing Platelet Rich Plasma (PRP), Whole Blood (WB) and Fibrin Glue (FG). Migration studies were performed using passage 2-4 synovial MSCs in trans-well migration assay. MSC migration, over a five hour period, was compared between PRP and pooled human Platelet Lysate (hPL). RESULTS: Ex-vivo mechanical agitating of the synovium with the cytology brush compared to irrigation alone increased MSC number 2.7-fold (n=10, p=0.002). Irrigation during arthroscopy was seen to effectively remove the majority of CFU-Fs for the synovial fluid. Use of a custom designed synovial brush, compared to the cytology brush resulted in a median 65-fold increase in the number of CFU-Fs (n=8, p=0.0148). Trilineage differentiation of released synovial MSCs was at least comparable to donor match synovial fluid MSCs. These MSCs adhered to clots within 30 minutes with no difference seen between clot compositions. Released synovial MSCs demonstrated a trend for a better migration towards hPL compared to PRP. CONCLUSIONS: Existing surgical procedures wash away SF-MSCs. Using a novel brushing technique and a custom designed synovial brush, synovial MSCs can be mechanically released in vivo, and these cells were capable of migration and rapid adhesion to clots. Collectively these findings aid in the rapid replenishment of endogenous minimally manipulated MSCs, and provide a one-stage procedure combining synovial brushing with microfracture, as a strategy for cost effective joint repair.